THE INFLUENCE OF TRAINING AND CAREER DEVELOPMENT ON EMPLOYEE PERFORMANCE IN KARAWANG DISTRICT - Farah Nur Auliya; Sari Marliani; July Yuliawati (Journal Of Resource Management, Economics And Business, 2024)
Purpose: To analyze the effect of training and career development on employee performance at BKPSDM Karawang Research Methodology: This study employed a quantitative descriptive verification method. The population consisted of 53 employees, with all employees included using saturated sampling. Data analysis was conducted using multiple linear regression through SPSS v.25 software. Results: The results of this study show that there is a partial influence on the training variable which has a significant effect on the employee performance variable. There is a partial influence on the career development variable which has a significant effect on employee performance. There is a simultaneous influence of training and career development which together have a positive and significant effect on the performance of BKPSDM Karawang employees. Contribution: This research provides valuable insights into the relationships between training, career development, and employee performance in a local government office setting. The findings can inform management strategies to optimize employee performance by focusing on training programs and career development initiatives in similar public sector environments.